English as the Language of Trade, Finance and Technology in APEC: An East Asia Perspective - Erlinda M. Medalla; Dorothea C. Lazaro (Philippine Institute for Development Studies (PIDS), 2004)
The use of English language for cross-border communications is important in many areas of trade ranging from tourism to the trade in financial services. This is in order to build a stronger regional economy through freely and openly communicating with one another. However, the increasing involvement in trade, tourism and international relations among APEC Member countries where English is not spoken as the first language poses some problems and barriers in achieving aspired regional cooperation. Efforts have been made by the government to encourage the internalization of the English as a second language. This has become a trend in many developing countries specifically in the East Asia and notably in South East Asian. This paper provides a survey of these efforts made. The different models used may be used or bench marked by others but more importantly cooperation in exchanges of ideas, information and resources would greatly benefit this objective.
Keywords: 330; capacity building; English language; business language; working language; language barrier; language skill; language education; English economy; public education; trade language; Internationale Wirtschaftsbeziehungen; Sprachpolitik; Englisch (Sprache); Bildungspolitik; APEC-Staaten